KOMPARASI EFEK PEMBERIAN MINYAK JINTAN HITAM (Nigella sativa) DENGAN MINYAK ZAITUN (Olea europea) TERHADAP PENURUNAN GLUKOSA DARAH PADA MENCIT (Mus musculus) STRAIN Balb/c - Setyo Dwi Santoso; Imam Suryanto (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2017)
Diabetes mellitus is a disease in humans characterized by an increase in blood glucose levels exceeds the normal limits. Cumin oil and olive oil is an alternative drug to a decrease in blood glucose levels for people with diabetes mellitus. Cumin oil and olive oil has several compounds that can lower blood glucose levels in excess. This study was conducted in January 2015 for 3 weeks in PUSVETMA Surabaya. Animals used in the study were female mice 2-3 months old with an average weight of 20-25 grams of a much as 30 individuals. At a dosage of dextrose 40% is 0.4 cc/ head/ day and the dosage of cumin oil and olive oil is 0.7 cc/ head/ day. This a study conducted of mice that had been induced dextrose 40% by using a sample of a much as 30 female mice. The results of statistical independent t-test, there was no difference or both of the test sample may lower blood glucose levels among female mice were treated with cumin oil and treated with olive oil. While the results of the data was tested using SPSS statistical Paired t-test showed that effectively lower blood glucose levels are olive oil, because there is a significant difference between before and after administration of olive oil after 7 days of dosing.